2022
DOI: 10.17219/acem/146775
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Galp and alarin peptides on HPA axis gene expression and adrenal function: In vivo experiments

Abstract: Background. Many experimental data indicate interactions between peptides involved in the control of food intake, energy homeostasis and adrenocortical hormone release. Glucocorticoids stimulate or inhibit the secretion of orexigenic and anorexigenic peptides, which in turn are involved in the regulation of adrenal growth, structure and function. Galanin-like peptide (Galp) and alarin (Ala) are involved in the regulation of food intake. Galp and Ala mRNAs have already been shown to be present in the arcuate nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Zhuang et al consistently showed that central injection of alarin significantly ameliorates depression-like behaviors in the UCMS mouse model (28). Subsequently, the antidepressant properties of alarin were further confirmed by several other studies (11,27,66). However, the antidepressant-like effect of alarin has been shown to be dose-limited, with no remarkable effect at higher doses (at 2.0 nmol or higher).…”
Section: Regulatory Effects Of Alarin In Depressionmentioning
confidence: 90%
See 2 more Smart Citations
“…Zhuang et al consistently showed that central injection of alarin significantly ameliorates depression-like behaviors in the UCMS mouse model (28). Subsequently, the antidepressant properties of alarin were further confirmed by several other studies (11,27,66). However, the antidepressant-like effect of alarin has been shown to be dose-limited, with no remarkable effect at higher doses (at 2.0 nmol or higher).…”
Section: Regulatory Effects Of Alarin In Depressionmentioning
confidence: 90%
“…Therapeutically, antagonists of galanin receptor (GalR) sub-type 1 (GalR1) and GalR3, as well as agonists of GalR2 have been established to have an antidepressant-like effect by enhancing the activities of selective serotonin reuptake inhibitors (SSRIs) and promoting the availability of transcription factors (64,65). Importantly, recent research has reported that alarin, which is also localized in the brain areas linked with depression, like the medial amygdala and hypothalamus, has been demonstrated to have regulatory effects on depression-like behaviors in various animal models (11,(25)(26)(27)66).…”
Section: Regulatory Effects Of Alarin In Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The restored synaptic proteins are essential for the formation, maturation, and function of synapses, thereby alleviating depression ( 78 83 ). Alarin is also postulated to have an antidepressant-like effect via the inhibition of the overactivated HPA axis and normalizing the serum levels of crucial glucocorticoid hormones ( 27 , 84 ). Moreover, alarin may help alleviate depression by increasing the expression of brain-derived neurotrophic factor (BDNF) in the prefrontal cortex and hippocampus, which has antidepressant-like actions through neuroprotection and promoting synaptic plasticity ( 27 ).…”
Section: Role Of Alarin In Various Disease Conditionsmentioning
confidence: 99%
“…Alarin is a recently discovered 25 amino acid neuropeptide belongs to galanin peptides family and it is a variant transcript of the GALP gene and has a wide distribution in the brain and periphery [6]. Alarin exerts its main function in physiological processes such as feeding and water intake by activating pathways in hypothalamus and pituitary gland [7,8]. Beside the autonomic contribution of alarin it also has extra hypothalamic in uences.…”
Section: Introductionmentioning
confidence: 99%